Detection of a phosphorylated glycine-serine linker in an IgG-based fusion protein. Issue 1 (2nd January 2017) - Tyshchuk, Oksana; Völger, Hans Rainer; Ferrara, Claudia; Bulau, Patrick; Koll, Hans; Mølhøj, Michael
ABSTRACT: Molecular mass determination by electrospray ionization mass spectrometry of a recombinant IgG-based fusion protein (mAb1-F) produced in human embryonic kidney (HEK) cells demonstrated the presence of a dominant +79 Da product variant. Using LC-MS tryptic peptide mapping analysis and collision-induced dissociation (CID) and electron-transfer/higher-energy collision dissociation fragmentations, the modification was localized to the C-terminal serine residue of a glycine-serine linker [(G4 S)2 ] of a fused heavy chain containing in total 2 (G4 S)2 -linkers. The modification was identified as a phosphorylation (+79.97 Da) by the presence of a 98 Da neutral loss reaction with CID, by spiking a synthetic phosphoserine peptide, and by dephosphorylation with alkaline phosphatase. A thermolysin digest combined with higher-energy collision dissociation (HCD) positioned the phosphoserine to one specific glycine-serine linker of the fused heavy chain, and the relative level of phosphorylated linker was determined to be 11.3% and 0.4% by LC-MS when the fusion protein was transiently expressed in HEK or in stably transformed Chinese hamster ovary cells, respectively. This observation demonstrates that fusions with glycine-serine linker sequences should be carefully evaluated during drug development to prevent the introduction of a phosphorylation site in therapeutic fusion proteins.